How imperative are the Joneses? Economic growth between individual desire and social coercion - Oliver Richters; Andreas Siemoneit (Vereinigung für Ökologische Ökonomie (VÖÖ), 2017)
Worldwide, economic growth is a prominent goal, despite its severe conflicts with ecological sustainability. Are 'growth policies' only a question of political or individual will, or do 'growth imperatives' exist that make them 'inescapable'? And why do people consume ever more, even in 'rich' countries? These questions are of political relevance, discussed since long - and essentially contested, especially along the dimensions free will vs. social coercion, and 'socio-cultural' influences vs. 'economic' reasons. We carefully derive definitions of the key terms 'social coercion' and 'growth imperative', referring to the concept of methodological individualism. Based on the assumption derived elsewhere that an economic growth imperative actually exists, we analyze some socio-cultural influences on individual behavior, dividing the debate in three subgroups. On the demand side, we study why people seemingly consume beyond basic needs to compare with others for social and cultural reasons, or to increase opportunities, while on the supply side, we analyze why people work more than needed given their consumption plans. When socio-cultural influences are truly forceful, they are usually based on economic pressure. Also, accumulation and certain consumption decisions can be traced back to quite 'rational' motives, making an often demanded 'cultural transformation' towards sufficiency a difficult project. Reproductive considerations (mating) and technology as households' investment may be considerably underestimated as consumption motives, the second probably causing a positive feedback loop. We conclude that, with regard to inescapability, socio-cultural mechanisms are secondary, compared with economic pressure on individuals. – – Weltweit ist Wirtschaftswachstum vorherrschendes Ziel, trotz ernsthafter Konflikte mit ökologischer Nachhaltigkeit. Ist 'Wachstumspolitik' nur eine Frage des politischen oder persönlichen Willens, oder gibt es 'Wachstumszwänge', die sie 'unausweichlich' machen? Und warum konsumieren Menschen immer mehr, selbst in 'reichen' Ländern? Diese Fragen sind politisch relevant, seit langem diskutiert - und hochumstritten, speziell entlang der Spannungslinien freier Wille vs. gesellschaftlicher Zwang sowie 'sozio-kultureller Einflüsse' vs. 'ökonomische' Gründe. Auf der Basis des methodologischen Individualismus leiten wir Definitionen der zentralen Begriffe 'gesellschaftlicher Zwang' und 'Wachstumszwang' her. Ausgehend von der anderswo begründeten Annahme, dass ein ökonomischer Wachstumszwang tatsächlich existiert, analysieren wir sozio-kulturelle Einflüsse auf individuelles Verhalten, wobei wir die Debatte in drei Untergruppen einteilen. Auf der Nachfrageseite untersuchen wir, warum Menschen scheinbar über ihre Grundbedürfnisse hinaus konsumieren, um sich mit anderen aus sozialen oder kulturellen Gründen zu vergleichen, oder um ihre Möglichkeiten zu erweitern. Auf der Angebotsseite eruieren wir, warum Menschen mehr arbeiten als zur Erfüllung ihrer Konsumwünsche notwendig ist. Wenn sozio-kulturelle Einflüsse wirklich zwingend sind, basieren sie zumeist auf ökonomischem Druck. Akkumulation und bestimmte Konsumentscheidungen können auf recht 'rationale' Motive zurückgeführt werden, was eine oft geforderte 'kulturelle Transformation' hin zu Genügsamkeit schwierig erscheinen lässt. Reproduktive Überlegungen (Partnersuche) und Technologie als Haushaltsinvestitionen werden als Konsummotive möglicherweise deutlich unterschätzt, und der zweite Punkt ist vermutlich verantwortlich für eine selbstverstärkende Rückkopplung. Wir kommen zu dem Schluss, dass - bezogen auf Unausweichlichkeit - sozio-kulturelle Mechanismen sekundär sind gegenüber ökonomischem Druck.
Keywords: Q01; O44; A13; 330; economic growth; growth imperative; social coercion; cultural drivers of growth; conspicuous consumption; Wirtschaftswachstum; Wachstumszwang; gesellschaftlicher Zwang; kulturelle Wachstumstreiber; Geltungskonsum